Beta-catenin expression in psoriasis - Mohamed Abd El-wahed Gaber; Mona Abd El-Halim Kandil; Shawki Mahmoud El-Farargy; Doaa Abd Elmoniem Galbet (Wolters Kluwer Medknow Publications, 2015)
Background: Psoriasis is a common inflammatory skin disease characterized by abnormal keratinocyte proliferation and differentiation. Beta-catenin participates in intercellular adhesion. Catenins are proteins found in complexes with cadherin cell adhesion molecules of cells. The role of catenin in regulating keratinocyte stem cell differentiation and hair follicle morphogenesis has been extensively reported. Aims and Objectives: is to study β-catenin expression in lesional and non-lesional psoriatic skin to throw light upon its possible role in the pathogenesis of psoriasis. Materials and Methods: Biopsies were taken from 20 patients with psoriasis vulgaris and from 10 normal controls. The distribution of Beta catenin was investigated using polycolonal rabbits B-catenin antibody-1 by immunohistochemical method. Results: In this study membranous β-catenin expression was significantly demonstrated in the control group then the non-lesional areas in comparison to the lesional areas (P < 0.001). Nuclear β-catenin staining expression was significantly more demonstrated in lesional and non-lesional areas in comparison to the control cases (P < 0.001). Conclusions: The down regulation of membranous β-catenin expression in lesional psoriatic skin might reflect a useful phenotypic marker of hyperprolifration of keratinocytes in psoriasis. Moreover, the mild down regulation of membranous β-catenin expression in non lesional psoriatic skin may provide clues about incipient structural abnormalities in the pathogenesis of psoriasis, providing an early diagnostic indicator for evolution to a generalized form of the disease. Nuclear β-catenin expression was not found in the control group but was demonstrated in lesional and moderately in non-lesional reflecting its role in kerationcyte proliferation.